The aging of precursors of supported platinum catalysts - Choren, Eduardo; Homez, Isabel; Zárraga, Jeannette; Buriel, Marianella (Rev. Téc. Fac. Ing. Univ. Zulia)
The behavior of alumina supported platinum calalysts is different from those supported on silica. The UV-Vis. diffuse reflectance and catharometric and gravimetric temperature programmed reduction study allowed the characterization of precursors (the support impregnated with the metal complex, without other treatment). These ones present, also, different properties that change during aging: the adsorption of the complex (H2PtCl6) supported on silica is relatively weak (it is washable by water), it conserves octahedric symmetry and suffers extensive exchange of chloro ligand with support hydroxo or aquo. That adsorbed on alumina suffers an extensive symmetry destruction and a lesser ligand exchange. Evidences are collected that metal conserves a strong dispersing interaction after reduction.